“AFRICAN SCULPTURE”, by William Fagg and Margaret Plass. 160 pp., fully illustrated with photographs. Studio Vista. London. 18/-. - Tracey, Hugh (International Library of African Music, 1964)
pages: 120-121
Keywords: African Music